Peran Pesantren dalam Menentang Imperialisme di Indonesia : Perlawanan Santri - yasmin, hawa arini dina (Maliki Interdisciplinary Journal, 2025)
Pesantren as a traditional Islamic educational institution has an important role in the Indonesian nation's struggle against imperialism. Santri not only learn religious knowledge, but also become the next generation and part of the resistance force against colonization during the Dutch and Japanese colonial periods. Santri and kiai became part of the people's power that actively rejected the domination of the Dutch and Japanese colonizers through da'wah, education, and socio-political action. There are figures such as Buya Hamka who played a role through thoughts and writings that aroused the spirit of independence, while KH. Wahid Hasyim combined Islamic values and nationalism in the community and state movements. Using a qualitative approach and literature study, this article shows that Islamic boarding schools and Islamic figures play an important role in maintaining the nation's identity and are part of helping the struggle for Indonesian independence.